PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN AUTOGRAPH TERHADAP KEMAMPUAN BERPIKIR KOMPUTASI SISWA PADA MATERI STATISTIKA SMP - Aritonang, Griselda; Simanjuntak, Erlinawaty (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
This study5aims to find5out5whether3there5is an influence of the Problem Based Learning model assisted by Autograph on students computational thinking skills in junior high5school5statistics materials. This research5was conducted5at Methodist Private Junior High School 12 Medan T.A 2023/2024.Â The research method5used is the quasi experiment method. The sample in this study consists of two classes, namely5class VIII-A as an experimental class and class VIII-B as a control5class.Â Based on the results of the study, it was obtained t_hitungt_tabelÂ (6,3141,686) which means that there was an influence of the Autograph-assisted Problem Based Learning model on the computational thinking ability of grade VIII students at Methodist 12 Medan Private Junior High School and the Autograph-assisted Problem5Based Learning model had an effect on5students' computational thinking ability of 1,995 (big effect).